PATTERN OF CHANGE IN THE FREQUENCY OF HELICOBACTER PYLORI WITH PERFORATED DUODENAL ULCER - Aman, Zahid; Naeem, Muhammad; Khan, Raza Muhammad; Ahmad, Tariq; Alam, Muhammad; Noreen, Sarwat; Khan, Muhammad Kamran (Journal of Ayub Medical College Abbottabad, 2008)
Background: Peptic ulcers were believed to be caused by stress, dietary factors, and gastric acid, but the link between H. pylori and peptic ulcers was identified in 1983. To see the frequency of Helicobacter pylori infection in patients with perforated duodenal ulcer and advise eradication therapy in these patients. This cross sectional study was conducted in Surgical Unit Hayatabad Medical Complex, Peshawar, during January 2007-June 2008. Methods: A total of 50 cases were included in the study. All cases presenting to our unit with acute perforated duodenal ulcer were recruited. After resuscitation and baseline investigations, all underwent emergency laparotomy via upper midline incision, after thorough peritoneal lavage, the perforation margins were freshened and closed over an omental patch. Serum from every patient was tested for H. pylori and accordingly managed. Results: Out of the 50 cases, 45 were males, and 5 were females. Age ranged from 20- 80 years old. All patients underwent emergency laparotomy. Postoperatively, all were started on PPI treatment and serum testing for H. pylori was done. Thirty-four (68%) turned out positive and 16 (32%) were found to be negative for H. pylori. Conclusion: There is still a high frequency of H. pylori infection in patients with perforated duodenal ulcer. But comparing these results with the various data available, there is a significant decline in H pylori positive perforated duodenal ulcer patients. Keywords: Peptic ulcer, Helicobacter pylori infection, Proton pump inhibitors